Capture-recapture method: traffic accident estimation along the circumferential road 5, national capital region, Philippines. (7th October 2012) - Martinez, R; Go, J; Timbang, T
Abstract : Background: Road traffic accidents are one of the world's largest contributors to injury problems, loss of lives, and damage to property. In the Philippines, accidents consistently remain one of the leading causes of morbidity and mortality. Objectives: The study is aimed to obtain a picture of road traffic accidents by using capture-recaptured method and to calculate an ascertainment corrected number of fatal and non-fatal injury that happened along C-5 Road, National Capital Region from January to December 2008. Methods: A Cross-sectional Study was done. A two-sample capture-recapture method was used to estimate traffic accidents. The first capture was all deaths and injuries due to road accidents reported by the Metro Manila Development Authority through their MMARAS Registry. The recapture will be all medico-legal and emergency records from the public hospitals. Results: For non-fatal road accidents, aggregate data showed 820 cases yielding 7.3/100 000 populations. When captured-recapture technique was used, a total of 2068 cases were recounted, representing 18.4/100 000 populations. For fatal injuries, aggregate data resulted to 15 new cases. Using capture-recapture method, 20 deaths were recounted, yielding 0.18/100 000 population. Case Fatality Rate is 0.97%. Conclusion/Significance: It was recommended to harmonise the sources of road accident data and to strengthen the Philippine National Injury Surveillance System. The study was presented to the Philippine Department of Health and contributed to build the Philippine Network on Injury Data Management System.